Healthy Eating for Elders: Salad Suggestions - Jennifer Hillan (EDIS)
Salads are quick and easy to make and have endless possibilities! Paired with whole grain crackers or bread, salads make healthy and convenient meals. Try some of the ideas in this leaflet for your next salad. This document, FCS8696-Eng, is one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.